Contemporary Islamic Jurisprudence Study on Inheritance from the Perspective of Islamic Law - King Albar Pandapotan Simatupang; Bunga Amalia Nasution (ISNU Sumatera Utara, 2025)
Inheritance law is an important part of Islamic jurisprudence (fiqh muʿāmalah) and holds a strategic position in Islam, as it regulates the transfer of property from a deceased person to his or her heirs in a fair and proportional manner. Normative Islamic inheritance provisions are regulated in detail in the Qur'an and Hadith, and further explained by scholars through the discipline of faraidh. However, the ever-evolving social, economic, and cultural dynamics demand a reexamination of the application of inheritance law in the context of modern life. The development of contemporary society presents various inheritance issues that have not been fully addressed in classical fiqh, such as the division of joint property between husband and wife, the inheritance of adopted children, the role of women in the family economic structure, the banking system and digital assets, and the plurality of legal systems prevailing in various Muslim countries. These conditions often create tension between the normative provisions of inheritance fiqh and the social realities faced by Muslims today. This study discusses inheritance law in classical Islamic fiqh and the challenges of its implementation in a modern context. Inheritance is regulated in detail in the Qur'an, Hadith, Ijma' and Qiyas, and is based on the principles of proportional justice and legal certainty. This study uses a literature review method with a qualitative descriptive approach. The results show that social and technological dynamics, such as adoption, in vitro fertilization, and interfaith marriage, give rise to new issues that need to be addressed through a contextual approach of maqashid sharia and ijtihad. Thus, Islamic inheritance law must continue to be studied to remain relevant and able to provide social justice in line with current developments. This study also emphasizes the importance of inheritance law education for the community to ensure that inheritance is carried out in accordance with sharia and avoids family conflict.